Bibliotecário empreendedor: habilidades e competências para eficiência na gestão - PEREIRA, Karem Kercterem Sá (2018)
It approaches as the profile of the librarian changed after the introduction of the Information and Communication Technologies (ICTs) and how this professional sought to adapt to this new context, illustrating which characteristics delimit an entrepreneurial librarian profile within the librarian. It has as objective at in general terms to identify how abilities and competences that the professional librarian need own; and, in specific terms: a) realize bibliographical research about the theme entrepreneurship; b) develop one chart comparing theoretical conception of authors about entrepreneurship with abilities and competences defined in Course Pedagogical Project (CPP) of Library Science of UFPA; c) explore in two libraries, more specifically in Library Public Arthur Vianna and Central Library of UFPA in Belém/PA, the level of actions of entrepreneurship to products and services. They grew the methodological procedures in three stages: in first with the bibliographical research, based in authors as Blatmann and Rados (2017), Chiavenato (2007), Drucker (1987), Filion (1999), Paiva Jr. and Cordeiro (2002), Rocha and Araujo (2017), and one Sebrae report (2017) about entrepreneurship in Brazil. In second stage, started an descriptive study of quali-quantitative approach, with interview containing questions open and closed with librarians of Central Library of UFPA and Library Public Arthur Vianna. It was verified that the selected librarians have almost all abilities and competences of profile of the entrepreneurial librarian but, he’s not see with entrepreneurial in the work. It concludes understanding that the encouragement of bosses are essential at the process of innovation in libraries; the new profile of librarian is reflex of user behavior in process of search of the information; and the profile of the entrepreneurial librarian is reflex to professional attitude in the face of difficulties of the profession.